Living in the Telling: Indigenous Storytelling of Post–COVID Desires for Academia - Funaki-Cole, Hine; MacDonald, Liana; Knox, Johanna; McKinnon, Daniel (Art/Research International)

(untitled) (University of Alberta, 2024)
Stories provide listeners or readers a doorway to understand the storyteller’s context and live in the telling. We, as Māori Indigenous scholars (doctoral students, researchers, and academics), bring together our stories, in the forms of creative nonfiction and poetry located in Aotearoa New Zealand and Te Whenua Moemoeā Australia, to tell the ways we navigate colonial spaces while also imagining our desired future. Centring Indigenous storytelling methods and sensory ethnography, we bring together the interrelatedness that situates our stories across time and place. The next wave of Indigenous researchers will be stepping into these spaces that we now walk, so it is timely and crucial that we find creative ways to provide clearer direction for them. We tell our stories in this paper as an act of hope that our stories might spark a fire in the reader’s heart to also tell theirs.